COMPREHENSIVE ORTHODONTIC TREATMENT OF PALATALLY IMPACTED MAXILLARY CANINES: PERAWATAN ORTODONTI KOMPREHENSIF KASUS IMPAKSI KANINUS DI REGIO PALATAL - Ervina Sofyanti (TALENTA, 2013)
Comprehensive orthodontic treatment among adult patients that required multidisciplinary approaches has been increased since a lot of them could not avail themselves with any treatment decades ago. Treatment of impacted canine in adult orthodontic patient needs to be integrated into the overall orthodontic treatment scheme. The following case report described an orthodontic treatment of 33-year-old woman with convex profile, palatally impacted of left maxillary canines and single dental crossbite. Dental midline shift associated with narrow arch form of upper arch and asymmetric tooth amount. Management of this case was started by extraction of first upper premolars in the opposite site from impacted maxillary in order to overcome dental discrepancy problem. Surgical exposure allowed the potency natural eruption of the impacted tooth. After 24-months of treatment, the impacted maxillary canines took place as integral elements in dentition and Class I Canine relationship was achieved. The success of this comprehensive orthodontic treatment also considered biomechanical and periodontal condition during treatment based on proper evaluation and good prognostic of the impacted tooth position. Providing adequate space and surgical exposure during levelling aligning phase followed by orthodontic traction and gingivectomy, were the multidisciplinary approaches of this following case. In conclusion, biomechanical orthodontic treatment related to periodontal condition must be considered in comprehensive orthodontic treatment of adult patient.